2006
DOI: 10.1177/0091270006291623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypericum perforatum on Ivabradine Pharmacokinetics in Healthy Volunteers: An Open‐Label, Pharmacokinetic Interaction Clinical Trial

Abstract: The effects of the CYP3A4 inducer, Hypericum perforatum, on the pharmacokinetics of a single oral dose of ivabradine were assessed. An open-label, 2-period, nonrandomized, phase-I, pharmacokinetic interaction design was used. Twelve healthy volunteers received a single oral dose of ivabradine (10 mg) followed by H perforatum (300 mg orally, 3 times a day) for 14 days, combining the last dose with another single dose of ivabradine. Pharmacokinetic data for ivabradine (S16257) and its main active metabolite (S18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…5-HT re-uptake inhibitors, 5-HT ligands). St. John’s wort has been shown to clinically interact with a number of conventional drugs mostly via these pharmacokinetic and/or pharmacodynamic mechanisms; such interactions take place with immunosuppressants (cyclosporine, tacrolimus, prednisone), hormones (oral pill, tibolone), cardiovascular drugs (the anticoagulants warfarin and phenprocoumon, the cardiac inotropic drug digoxin, the antilipidaemic drugs simvastatin, rosuvastatin and atorvastatin, the calcium blockers nifedipine and verapamil, the β 1 -adrenoreceptor blocker talinolol, the anti-anginal drug ivabradine), antiretroviral drugs (indinavir, nevirapine), anticancer drugs (irinotecan, imatinib), drugs acting on the CNS (anaesthetics, the anxyolityc drugs alprazolam, midazolam, quazepam and buspirone, the antidepressants sertraline, nefazodone, paroxetine, venlafaxine and amitriptyline, the anti-epileptic drugs mephenytoin, drugs for addicted patients, such as methadone and bupropion, the centrally acting muscle relaxant chlorzoxazone, the antitussive drug dextromethorphan), anti-ulcer medications (omeprazole), antidiarrhoeal drugs (loperamide), drugs acting on the respiratory system (theophylline, fexofenadine), antifungal drugs (voriconazole) and antimigraine medicines (eletriptan) [55,56,143,146,147,148,149,150,151,154,162,163,164,165,166,167,168,169,170,171,172,173,174,175,176,177,178,179,180,181,182,183,184,185,186,187,188,189,190,191,192,193,194,195,196,197,198,199,200,201,202,203,204,205,206,207,208,209,210,211,212,213,214,…”
Section: Clinical Interactions Between Herbs and Conventional Drugsmentioning
confidence: 99%
“…5-HT re-uptake inhibitors, 5-HT ligands). St. John’s wort has been shown to clinically interact with a number of conventional drugs mostly via these pharmacokinetic and/or pharmacodynamic mechanisms; such interactions take place with immunosuppressants (cyclosporine, tacrolimus, prednisone), hormones (oral pill, tibolone), cardiovascular drugs (the anticoagulants warfarin and phenprocoumon, the cardiac inotropic drug digoxin, the antilipidaemic drugs simvastatin, rosuvastatin and atorvastatin, the calcium blockers nifedipine and verapamil, the β 1 -adrenoreceptor blocker talinolol, the anti-anginal drug ivabradine), antiretroviral drugs (indinavir, nevirapine), anticancer drugs (irinotecan, imatinib), drugs acting on the CNS (anaesthetics, the anxyolityc drugs alprazolam, midazolam, quazepam and buspirone, the antidepressants sertraline, nefazodone, paroxetine, venlafaxine and amitriptyline, the anti-epileptic drugs mephenytoin, drugs for addicted patients, such as methadone and bupropion, the centrally acting muscle relaxant chlorzoxazone, the antitussive drug dextromethorphan), anti-ulcer medications (omeprazole), antidiarrhoeal drugs (loperamide), drugs acting on the respiratory system (theophylline, fexofenadine), antifungal drugs (voriconazole) and antimigraine medicines (eletriptan) [55,56,143,146,147,148,149,150,151,154,162,163,164,165,166,167,168,169,170,171,172,173,174,175,176,177,178,179,180,181,182,183,184,185,186,187,188,189,190,191,192,193,194,195,196,197,198,199,200,201,202,203,204,205,206,207,208,209,210,211,212,213,214,…”
Section: Clinical Interactions Between Herbs and Conventional Drugsmentioning
confidence: 99%
“…Ivabradine is extensively metabolized by intestinal and hepatic CYP3A4. A clinical study performed in healthy volunteers showed that administration of SJW significantly decreased ivabradine maximal plasma concentration (33 vs 15 ng/mL) and AUC (144 vs 44 ng h/mL) (83). Marginal influence on tolbutamide pharmacokinetics Weak or no effect on CYP2C9.…”
Section: Antianginal Drugsmentioning
confidence: 99%
“…An open-label, 2-period, nonrandomized, phase-I, pharmacokinetic interaction design was used by Portolés et al [34]. The authors observed a tendency toward shorter time to concentration in plasma and lower apparent half-life.…”
Section: Limitations To the Usementioning
confidence: 99%